Characterization of air–sea exchanges over the Western Mediterranean Sea during HyMeX SOP1 using the AROME–WMED model. (12th January 2015) - Rainaud, R.; Lebeaupin Brossier, C.; Ducrocq, V.; Giordani, H.; Nuret, M.; Fourrié, N.; Bouin, M.‐N.; Taupier‐Letage, I.; Legain, D.
Abstract : Air–sea exchanges play an important role during intense weather events over the Mediterranean Sea, especially in supplying heat and moisture for heavy precipitation events, which often affect the area. Observations collected during the first Hydrological cycle in the Mediterranean Experiment (HyMeX) Special Observation Period (SOP1) over the Western Mediterranean area in autumn 2012 provide an unprecedented dataset for assessing the capabilities of numerical weather prediction systems to represent the air–sea interface and marine boundary layer during the heavy precipitation season. A HyMeX‐dedicated version of Application de la Recherche à l'Opérationnel à Méso‐Échelle, in French (AROME) covering the whole western Mediterranean basin, named AROME–WMED, was evaluated through comparisons against moored buoys, drifting buoys and ship measurements deployed during the HyMeX campaign. A general, good agreement is found for near‐surface meteorological parameters, whereas significant discrepancies are observed during strong air–sea exchange periods. The two main reasons are that (1) sea‐surface temperature (SST) is kept constant during the model runs and (2) sensible heat flux is overestimated in strong wind regimes by the AROME turbulent flux parametrization. Air–sea exchanges during SOP1 were characterized thanks to AROME–WMED short‐range (1–24 h) forecasts. This shows some areas of strong air–sea fluxes in the Gulf of Lion and the Balearic, Ligurian and Tyrrhenian Seas. The Gulf of Lion is the area showing the highest variability of air–sea fluxes, due to dominant strong regional winds (Mistral/Tramontane). Whereas some heavy precipitation events occur without significant air–sea fluxes, all strong air–sea exchange events include, or occur only 1 or 2 days before, heavy precipitation events. A detailed analysis of an Intense Observation Period (IOP) dedicated to a heavy precipitation event (IOP13, from 12–15 October) illustrates how both dynamic (wind) and thermodynamic (temperature and humidity gradient effect) contributions influence air–sea flux evolution.